2012
DOI: 10.1073/pnas.1203617109
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90α (HSP90α), a substrate and chaperone of DNA-PK necessary for the apoptotic response

Abstract: The “apoptotic ring” is characterized by the phosphorylation of histone H2AX at serine 139 (γ-H2AX) by DNA-dependent protein kinase (DNA-PK). The γ-H2AX apoptotic ring differs from the nuclear foci patterns observed in response to DNA-damaging agents. It contains phosphorylated DNA damage response proteins including activated Chk2, activated ATM, and activated DNA-PK itself but lacks MDC1 and 53BP1, which are required to initiate DNA repair. Because DNA-PK can phosphorylate heat shock protein 90α (HSP90α) in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 52 publications
3
85
0
Order By: Relevance
“…In support of this conclusion, it was reported that Hsp70 protects against oxidative-induced cellular injury through improving cell endogenous antioxidant stability (Afolayan et al 2014). As another contributing factor, Solier et al (2012) provided evidence for proapoptotic phosphorylation and activation of Hsp90 in an in vitro context. Moreover, altered kinase activity has been subjected to pathologic events in Aβ toxicity, which is tightly regulated by Hsp90 (Luo et al 2008 GA-inhibited Hsp90 protective pathways in Aβ-induced neuronal toxicity and long-term memory impairment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In support of this conclusion, it was reported that Hsp70 protects against oxidative-induced cellular injury through improving cell endogenous antioxidant stability (Afolayan et al 2014). As another contributing factor, Solier et al (2012) provided evidence for proapoptotic phosphorylation and activation of Hsp90 in an in vitro context. Moreover, altered kinase activity has been subjected to pathologic events in Aβ toxicity, which is tightly regulated by Hsp90 (Luo et al 2008 GA-inhibited Hsp90 protective pathways in Aβ-induced neuronal toxicity and long-term memory impairment.…”
Section: Discussionsupporting
confidence: 56%
“…In this manner, Hsp70 protein plays a role in suppressing apoptotic cascades by directly mediating the conformation of molecules involved in signal transduction, beyond chaperone activity in protein folding and stabilization (Lu et al 2002;Sabirzhanov et al 2012;Gallo 2006). Conversely, Hsp90 has been suggested to contribute to upregulation of proapoptotic factors (Solier et al 2012). Also, Hsp70 acts as a sensor of cellular redox changes and is involved in occupying the pocket of the chaperone protein (Miyata et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…S3). It could be the case that geldanamycin induced an apoptotic response, because rapid Hsp90a phosphorylation at Thr5 and Thr7 is induced in apoptotic cells (Solier et al, 2012). In our immunofluorescence analysis, this subset of cells was excluded.…”
Section: Heat Shock Induces Hsp90a Dissipation and Primary Cilia Resomentioning
confidence: 99%
“…Essentially, cells surviving a transient and reversible apoptotic response acquire permanent genetic changes and undergo oncogenic transformation (14). The dual activity of HSP90α described by Solier et al (2), associating its phosphorylation by DNA-PK at the H2AX apoptotic ring and the stabilization of the kinase during this process, could be crucial in ensuring complete HSP90α phosphorylation and consequent inhibition of its cytoprotective activity, given that the apoptotic ring is present (Fig. 1).…”
mentioning
confidence: 99%
“…Therefore, there is a need for direct sensors to ensure the correct completion of the apoptotic process. The work of Solier et al (2) contributes to our understanding of such complex control mechanisms by demonstrating an interplay between the heat shock protein chaperone (HSP90α) chaperone and the DNA-dependent protein kinase (DNA-PK) during apoptosis.…”
mentioning
confidence: 99%